PAMIN: An Innovative Interactive Magnetic Board Media to Enhance Alphabet and Counting Skills of 4–5-Year-Old Children - Hairani, Sarifah; Matheos Lasarus Malaikosa, Yes; Fitri, Ruqoyyah; Putri Setianingsih, Hesti; Nur Zuama, Shofiyanti (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Alphabet and counting skills are fundamental components in the development of early childhood literacy and numeracy. However, many children aged 4–5 are only able to memorize letters and numbers without understanding their concrete forms and meanings. This study aims to develop and examine the effectiveness of PAMIN (Interactive Magnetic Board) as a learning media to enhance alphabet and counting skills in early childhood. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), and was conducted at TK Dharmawanita Tawangsari 2, Sidoarjo. The study involved 23 children in Group A (aged 4–5 years). The instruments used included observation sheets, skill tests, and expert validation questionnaires. The results showed that PAMIN is feasible to use, based on validation by subject matter and media experts. Moreover, there was a significant improvement in both alphabet and counting abilities, with an average N-Gain score of 0.81 (classified as high). PAMIN proved to be effective as it integrates enjoyable multisensory learning through a combination of visual, manipulative, and singing methods. This study concludes that PAMIN is an innovative learning media and is recommended to support interactive learning processes in early childhood education.